Mapping the language of professional vision: exploring obstacles and strategies for stimulating a positive school climate in three Swedish middle schools - Silvia Edling; Robert Thornberg; Peter Gill; Maryam Bourbour; Davoud Masoumi (Education Inquiry)
A positive school climate is both pivotal for opposing bullying and other degrading treatment and dependent upon a whole-school approach. Although a growing body of research emphasises the importance of both teachers’ and staff’s professional vision and related concepts as vital elements in stimulating a positive school climate, surprisingly few studies have explored the nuances, significance and use of teachers’ and staff’s professional vision in this regard. Drawing from case-study methodology, the purpose of the article is to map the selective language of professional vision and its related concepts as expressed by 7 teachers and 19 staff members in 3 schools, purposefully selected in a Swedish municipality. Semi-structured interviews were coded using content analysis and a socio-ecological framework. Three general themes that intersected the professions emerged from the data: 1) the importance of seeing the pupils, 2) the importance of learning about seeing and 3) the importance of learning from seeing in practice. Highlighting the potential of professional vision as a transformative tool, the findings of this study shed light on the challenges and strategies for stimulating professional vision as a means of informed decision-making in fostering a positive school climate.